2020
DOI: 10.3389/fgene.2020.522831
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analyses of the Differentially Expressed Alternative Splicing Events in Gastric Cancer and Its Clinical Significance

Abstract: Accumulation of evidence has indicated a close relationship between alternative splicing (AS) and gastric cancer (GC), whereas systematic analyses of the differentially expressed AS events (DEAS) between GC and normal tissues are lacking. RNA-Seq data and the corresponding clinical information were downloaded from TCGA GC cohort. The percent spliced-in (PSI) value calculated in the GC tissues and normal tissues was employed to quantify the DEAS. Further, survival-associated DEAS and DEAS signatures were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Among these, most reports focus on the relationship between aberrant ASEs and prognosis and survival in cancer patients. After identification of the overall survival-associated ASEs, prognostic models were developed to predict the survival outcomes of patients with aberrant AS patterns in gastric cancer (32)(33)(34)(35), breast cancer (36), CHOL (37), glioblastoma (38), pancreatic cancer (39), LAML (40), UVM (41), HNSC (42), etc. Aberrant AS is also related to chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, most reports focus on the relationship between aberrant ASEs and prognosis and survival in cancer patients. After identification of the overall survival-associated ASEs, prognostic models were developed to predict the survival outcomes of patients with aberrant AS patterns in gastric cancer (32)(33)(34)(35), breast cancer (36), CHOL (37), glioblastoma (38), pancreatic cancer (39), LAML (40), UVM (41), HNSC (42), etc. Aberrant AS is also related to chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…AS is the basic mechanism of gene expression regulation in eukaryotes, which increases the complexity of gene expression, promotes higher transcription e ciency, and protein diversity [15]. It has been found that the dysregulation of DEAS in cancer-related genes is involved in many biological processes of tumors, and these abnormally regulated genes can be used as molecular markers for cancer prognosis and treatment [16,17]. However, a comprehensive analysis of DEAS signatures in GBM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These events have been discovered in the context of physiological diseases and some biological processes. 10,11 Splice variants are responsible for diversifying gene expression regulation, which functionally result in the diversity of proteomes and contribute to cell proliferation, migration, or immune escape. [12][13][14] According to the previous description, some compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%